2018
DOI: 10.1016/j.tcr.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury without radiological abnormality (SCIWORA) manifested as self-limited brown-SEQUARD syndrome

Abstract: IntroductionCombination between SCIWORA and Brown-Sequard syndrome in a patient is a rare condition. In SCIWORA, there is usually a delay in neurologic deficits which can potentially lead to misdiagnosis. Therefore, the clinician should have a good understanding of the course of the disease to make a good diagnosis and treatment.Case reportReporting a case of female 20 years old with chief complaint of severe neck pain and delayed limbs weakness. The mechanism of injury was fall with the head hit the ground in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The case of a young woman has been reported who fell and hit her head on the ground first in the left lateral flexion position, and her symptoms manifested as BSS. 8 In our case, the patient's clothing was caught in a rapid autorotation machine, causing the body to rotate axially. This powerful twisting force caused the thoracic spinal cord to be rotation-stretched rather than stretching along the long axis of the spinal cord.…”
Section: Discussionmentioning
confidence: 83%
“…The case of a young woman has been reported who fell and hit her head on the ground first in the left lateral flexion position, and her symptoms manifested as BSS. 8 In our case, the patient's clothing was caught in a rapid autorotation machine, causing the body to rotate axially. This powerful twisting force caused the thoracic spinal cord to be rotation-stretched rather than stretching along the long axis of the spinal cord.…”
Section: Discussionmentioning
confidence: 83%
“…Further complications, such as wound infection, meningitis, and sepsis should be treated accordingly [ 16 ]. However, Sakti et al [ 17 ] reported treating BSS associated with spinal cord injury without radiological abnormalities conservatively with a cervical collar, with dramatic improvements occurring within hours [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the negative impact of Central Nervous System (CNS) injuries on somatic growth in children is well established [24], even mild neurological sequelae suffered at a young age will have repercussions on orthopaedic development in the medium to long term [25], especially progressive neuromuscular scoliosis [26]. Second, the possibility of the development of intraspinal tissue damage resulting from the development of gliosis and/or syringomyelia [27] leading to unexpected and unexplained long-term neurological impairment, even in the case of only transient or mild initial neurological signs and symptoms have been addressed both among pediatric [28,29] and adult population [30]. Syringomyelia is recognized as the main factor of neurological deterioration following SCI, since MRI has improved the diagnosis, but the correlation between the severity of SCI and the incidence of Post-Traumatic Syringomyelia (PTS) or the time interval to its onset is controversial [30].…”
Section: Oproj0006978(5)2021mentioning
confidence: 99%